Impact Assessment of Non-Governmental Organization Development at Fugar, Nigeria (Global Journal of Human-Social Science, 2018)
Over the years, it has been observed that Non-Governmental Organizations (NGOs) has increased their development profiles at local, national and international levels. NGOs have come to be recognized as important actors on the landscape of development on health, education, provision of water, construction of school buildings in Nigeria. The major aim of this study is to assess the impact of Non-Governmental Organization in community development in community and some of the objectives of the paper are to assess the socio-economic and infrastructural development impact Non-Governmental organization has made in rural communities and identifies the major areas Non-Governmental organization has really impacted on rural communities. Taking inventory of the impacts of NGOs in other countries, the 'Tanzania Education Network has embarked on over 5 educational programs which have benefited close to 100,000 students and more than 850 teachers to date. These include: The Madrasa Pre-School program, the School Improvement Programmes, the International Academic Partnership, the Aga Khan Education Service Tanzania and the Coastal Rural Support Program. While in Nigeria a lot of projects like health, education and infrastructure were executed by NGOs in this regard, more is expected to be put in place by the growing number of NGOs in Nigeria, for the overall wellbeing of the society.
Keywords: non-governmental organizations; community development; programmes; collaboration; nigeria